Effect of Perozonation on Biodegradability and Toxicity of a Penicillin Formulation Effluent - Cokgor, Emine Ubay; Karahan, Ozlem; Arslan-Alaton, Idil; Meric, Süreyya; Saruhan, Hande; Orhon, Derin (Informa UK Limited, 2006)
The pretreatment of synthetic penicillin formulation effluent containing Procain Penicillin G (PPG) with the O(3)/H(2)O(2) process (applied ozone dose = 1440 mg h-1 treatment time = 60 minutes; pH 7; H(2)O(2) = 10 mM) was investigated. The effect of chemical pretreatment was assessed on the basis of acute toxicity and biodegradability with activated sludge using water flea Daphnia magna toxicity and activated sludge inhibition tests. Biological treatability studies were performed with a mixture of untreated or pretreated PPG effluent (25% on volume basis) and synthetic domestic wastewater simulating readily biodegradable organic substrate to simulate the characteristics of domestic wastewater (75% on volume basis). Pretreatment of PPG effluent the O(3)/H(2)O(2) process resulted in more than 70% chemical oxygen demand (COD) removal and a 50% decrease in the acute toxicity towards Daphnia magna. On the other hand, biodegradation of untreated PPG effluent needed prolonged acclimation periods to obtain a significant biological COD removal (= 80%). Pretreatment employing the O(3)/H(2)O(2) process not only decreased the ultimate biodegradability of PPG effluent but also increased its inhibitory effects on activated sludge treatment speculatively due to the formation of less biodegradable oxidation by-products.
Keywords: Time Factors; Sewage; Penicillin G Procaine; Waste Disposal, Fluid; Water Purification; Oxygen; Biodegradation, Environmental; Ozone; Daphnia; Animals; Water Pollutants, Chemical